DEVELOPING TEACHERS’ PEDAGOGICAL COMPETENCE THROUGH ENGLISH SUBJECT TEACHERS’ WORKING GROUP (MGMP) - Haliza Haliza; Nani Hizriani; Hidayah Nor (LET: Linguistics, Literature and English Teaching Journal, 2021)
This study is aimed to determine how is the contribution of English Subject Teachers’ Working Group (MGMP) in developing teachers’ pedagogical competence and how the teachers perception on that contribution. The method used in this study was descriptive qualitative. The data was collected through interview and documentation. The subjects of this study were 9 teachers, they were the head, treasurer, and 7 members of the MGMP forum. The result showed that the English MGMP gave a good contribution to the development of teachers’ pedagogical competence. The contribution of the MGMP in developing teachers’ pedagogical competence was carried out through the involvement of various parties and MGMP programs itself. In every activity, MGMP usually presented external speakers such as lecturers from several universities. Besides, the result of this study also showed that the English teachers gave a positive perception on the contribution of MGMP in developing teachers’ pedagogical competence. The teachers considered that the MGMP as a community gave a big contribution in develoving their competence. Through MGMP activities, the teachers discussed to solve the problems they faced, communicated each other, and exchanged experiences.